The first troglobitic species of Perigona Castelnau, 1835 endemic to southeastern Brazil (Carabidae, Perigonini) - Pellegrini, Thais Giovannini; Ferreira, Rodrigo Lopes; Vieira, Letícia (European Journal of Taxonomy, 2022)
We describe the first Neotropical troglobitic species of the genus Perigona Castelnau, 1835 from specimens collected in eight caves located in the Arcos-Pains-Doresópolis speleological province (APD), southeastern Brazil. Perigona spelunca sp. nov. is the fourth known microphthalmous species of the genus, and the second of the subgenus Neoperigona. Other specialisations to the subterranean environment include brachyptery, elongation of appendages and orangish brown body coloration. The new species has an umbilicate series of punctures on the 8th stria with 15 setae arranged linearly and not divided in three groups. We also provide historic biogeographical remarks on the new species.